Assessment of the Anterolateral Ligament of the Knee by Magnetic Resonance Imaging - De Carli, Angelo; Monaco, Edoardo; Mazza, Daniele; Argento, Giuseppe; Redler, Andrea; Proietti, Lorenzo; Gaj, Edoardo; Ferretti, Andrea (Joints, 2018)
Purpose The purpose of this study was to describe the anatomy of the anterolateral ligament (ALL) of the knee by the use of 1.5 Tesla (T) magnetic resonance imaging (MRI) in a series of young patients without knee injuries.Methods Subjects aged 18 years or older without an anterior cruciate ligament injury, as confirmed on MRI, were included. MRI examinations were all performed on 1.5 T scans. The ALL was defined as the low signal band originating from the region of the lateral epicondyle of the femur, crossing the proximal surface of the lateral collateral ligament, deep to the iliotibial band, and inserting onto the tibia between the Gerdy's tubercle and the fibular head.Results Twenty-six patients met the eligibility criteria and were enrolled into the study. In one patient, it was not possible to visualize the ALL. In all the other subjects, the ligament originated anterior and distal to the lateral epicondyle and inserted on the proximal tibia approximately 5 mm below the joint line and just distal to the Gerdy's tubercle. It had an average length of 33 ± 1.2 mm, an average width of 5.5 ± 0.3 mm, and an average thickness of 2 mm.Conclusion The ALL is a distinct structure of the anterolateral capsule that can be easily identified using 1.5 T MRI scans.Level of Evidence This is a level IV, observational study.
Keywords: anterolateral ligament; anatomy; imaging; magnetic resonance